KOMPARASI PENDAPATAN USAHATANI PADI BERDASARKAN PENGGUNAAN BENIH DI KECAMATAN SUNGAI KAKAP KABUPATEN KUBURAYA - Ekawati; Reiza Darmawan; Rahmatullah Rizieq (Jurnal Ekonomi STIEP, 2023)
This study aims to compare rice farming income between those using certified and non-certified seeds. The results of this study can provide an overview of the income farmers will obtain if they use certified seeds. The research was conducted in Sungai Kakap village, Sungai Kakap sub-district, Kubu Raya Regency. Most rice is produced in this area, so it was chosen as the research location. The research sample consisted of 30 farmers consisting of 22 farmers using non-certified seeds and eight farmers using certified seeds. The research data is processed so that RC Ratio can be obtained and continued with the different tests between income. The results showed that the income from rice farming with certified seeds was higher than non-certified seeds. However, the value of the RC ratio for farms with non-certified seeds is higher. The t-test results concluded that there is a significant difference between farm income using certified and non-certified seeds statistically. Finding certified seeds that will increase production and save costs is advisable. The four farmers are also advised to be able to use certified seeds in their farming business